European guideline (EuroGuiDerm) on atopic eczema: part I – systemic therapy. (18th August 2022) - Wollenberg, A.; Kinberger, M.; Arents, B.; Aszodi, N.; Avila Valle, G.; Barbarot, S.; Bieber, T.; Brough, H.A.; Calzavara Pinton, P.; Christen‐Zäch, S.; Deleuran, M.; Dittmann, M.; et al.
Abstract: The evidence‐ and consensus‐based guideline on atopic eczema was developed in accordance with the EuroGuiDerm Guideline and Consensus Statement Development Manual. Four consensus conferences were held between December 2020 and July 2021. Twenty‐nine experts (including clinicians and patient representatives) from 12 European countries participated. This first part of the guideline includes general information on its scope and purpose, the health questions covered, target users and a methods section. It also provides guidance on which patients should be treated with systemic therapies, as well as recommendations and detailed information on each systemic drug. The systemic treatment options discussed in the guideline comprise conventional immunosuppressive drugs (azathioprine, ciclosporin, glucocorticosteroids, methotrexate and mycophenolate mofetil), biologics (dupilumab, lebrikizumab, nemolizumab, omalizumab and tralokinumab) and janus kinase inhibitors (abrocitinib, baricitinib and upadacitinib). Part two of the guideline will address avoidance of provocation factors, dietary interventions, immunotherapy, complementary medicine, educational interventions, occupational and psychodermatological aspects, patient perspective and considerations for paediatric, adolescent, pregnant and breastfeeding patients.